Emotional words can be embodied or disembodied: the role of superficial vs. deep types of processing - Abbassi, Ensie; Blanchette, Isabelle; Ansaldo, Ana I.; Ghassemzadeh, Habib; Joanette, Yves (Frontiers in Psychology, 2015)
Emotional words are processed rapidly and automatically in the left hemisphere (LH) and slowly, with the involvement of attention, in the right hemisphere (RH). This review aims to find the reason for this difference and suggests that emotional words can be processed superficially or deeply due to the involvement of the linguistic and imagery systems, respectively. During superficial processing, emotional words likely make connections only with semantically associated words in the LH. This part of the process is automatic and may be sufficient for the purpose of language processing. Deep processing, in contrast, seems to involve conceptual information and imagery of a word’s perceptual and emotional properties using autobiographical memory contents. Imagery and the involvement of autobiographical memory likely differentiate between emotional and neutral word processing and explain the salient role of the RH in emotional word processing. It is concluded that the level of emotional word processing in the RH should be deeper than in the LH and, thus, it is conceivable that the slow mode of processing adds certain qualities to the output.